Multi-Agent Systems: A Review Study - Jaleel, Hanan Qassim; Stephan, Jane Jaleel; Naji, Sinan A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Multi-agent systems are subfield of Artificial Intelligence that has experienced rapid growth because of its flexibility and intelligence in order to solve distributed problems. Multi-agent systems (MAS) have got interest from various researchers in different disciplines for solving sophisticated problems by dividing them into smaller tasks. These tasks can be assigned to agents as autonomous entities with their private database, which act on their environment, perceive, process, retain and recall by using multiple inputs. MAS can be defined as a network of individual agents that share knowledge and communicate with each other in order to solve a problem that is beyond the scope of a single agent. It is imperative to understand the characteristics of the individual agent or computing entity to distinguish a simple distributed system and multi-agent system. To solve each task, the agent can take the appropriate actions, decisions, and can cooperate with other agents to fulfill its goals or objectives. MAS has several applications including cloud computing, web advertisement, e-commerce, computer network, learning abilities, etc. This survey represents a comprehensive discussion of all aspects of MAS, and discusses an overview of MAS definitions, architecture, features, communications, organizations, and finally discusses the some of the real practical applications.